Vortex induced vibrations suppression for a cylinder with plasma actuators - Castro Hebrero, Federico Nicolás (2020)
We propose the use of plasma actuators in order to control the vortex induced vibration phenomena (VIV) originated by an airflow around a rigid circular cylinder. The body was placed in a closed loop wind tunnel and mounted on elastic supports that allowed small oscillatory movements in the transverse direction with respect to the free stream. Our goal was to suppress the vibrations that naturally occurred in this configuration. To this end, two plasma actuators were disposed symmetrically on the surface of the cylinder along the span that transferred momentum to the fluid by means of a dielectric barrier discharge. The experiments were performed by varying the free stream velocity and the actuation parameters, which means voltage and frequency were kept constant throughout our experiments. We characterised the dynamics of the system for experimental conditions by involving a high reduced mass m∗ ≈ O(103) and by considering a range of Reynolds numbers regarding the intermediate sub critical flow regime 1000 ≲ Re ≲ 10000. The reduced velocities lied within the range of 4.50 < Ur < 6.25. Our results show that the plasma actuators exhibit a large ability to suppress the VIV throughout the whole range of the experimental conditions tested. Complementary measurements undertaken with a particle image velocimetry (PIV) system enabled us to explain the outstanding performance observed.